Persepsi dan Tantangan Pembelajaran Koding dalam Mata Pelajaran IPA sebagai Penguatan Keterampilan Abad-21 - Barid, Siti Shofa Assyifa’ul Qulbi; Gunawan, Arvidhea Safira; Nur, Syinta (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2025)
Coding education in schools serves not only as a technical skill, but also supports the development of 21st-century skills such as critical thinking, problem solving, collaboration, creativity, and computational thinking. The purpose of this study is to analyze perceptions and challenges in coding education in science education. A systematic literature review using the PRISMA approach was used in this research. This study began with developing research questions, selection criteria, search strategies, research article selection processes, research article quality assessments, and synthesis of selected articles. Data were collected by identifying articles related to perceptions and challenges of coding learning in science subjects, covering 200 articles related to coding learning published between 2020 and 2025, and 12 articles that met the criteria were obtained. The results showed that coding learning integrated into science subjects in junior high school had a significant contribution to developing 21st-century skills. However, the challenges faced included a lack of teacher competence in coding, limited resources, and the unavailability of a curriculum that supported the systematic integration of coding. These findings emphasized the importance of teacher training and the development of educational policies that were adaptive to current technology.